Dutch Comfort: The Limits of AI Governance through Municipal Registers. - Cath, Corinne; Jansen, Fieke (Techné: Research in Philosophy & Technology, 2022)
In this commentary, we respond to the editorial letter by Professor Luciano Floridi entitled "AI as a public service: Learning from Amsterdam and Helsinki." Here, Floridi considers the positive impact of municipal AI registers, which collect a limited number of algorithmic systems used by the city of Amsterdam and Helsinki. We question a number of assumptions about AI registers as a governance model for automated systems. We start with recent attempts to normalize AI by decontextualizing and depoliticizing it, which is a fraught political project that encourages what we call 'ethics theater' given the proven dangers of using these systems in the context of the digital welfare state. We agree with Floridi that much can be learned from these registers about the role of AI systems in municipal city management. The lessons we draw, on the basis of our extensive ethnographic engagement with digital wellfare states, are distinctly less optimistic.